Health-care information systems adoption – a review of management practices - Emil Lucian Crisan; Alin Mihaila (Vilakshan (XIMB Journal of Management))
Purpose – The purpose of this paper is to provide practitioners and researchers a more condensed and structured perspective on the adoption of information management systems by the health-care industry, given the spread and the increased amount of research concerning the topic. Design/methodology/approach – This paper is a literature review. A Technology (What?) – Context and before adoption Analysis (When and Why?) – Implementation (How?) – Outcomes (What for?) framework is used to present the trends concerning information technology adoption in an accessible manner. Findings – The main finding is that small or large health-care organizations should no longer focus on information systems’ adoption but should adopt a digital transformation paradigm. By considering this paradigm, management practices related to information technologies’ adoption projects should be complemented by practices related to the continuous organizational changes and readaptation of the organizational strategy, to benefit the advantages information systems can offer. Practical implications – The main recommendation for health-care industry managers is to adopt specific practices to manage the digital transformation process of their organizations, as they should understand that it is no longer about adopting information technologies, but about managing the associated organizational change. Originality/value – Instead of focusing on specific information systems’ adoption as other papers do, this paper provides a holistic understanding of the information technologies and management practices which are used in the field.